New Remuneration System for Village Government Apparatus (APD): Can it Halt Fraud Incident(s)? - Mellani Yuliastina; Muhammad Hudaya; Wahyudin Nor; Basyirah Ainun (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: Central and local governments are trying to curbing fraud involving the village government apparatus (APD) by increasing the remuneration of APD, so that they are not tempted to misuse the village fund that they manage.Design/Methodology/Approach: The purpose of this study is to see whether remuneration is the cause of fraud, the extent to which the application of new PPE remuneration has an impact on reducing the potential for fraud and who is the main actor in fraud. This research uses a qualitative approach, and case study strategy research. The research was carried out in in three villages within a district, Regency of Barito Kuala, South Kalimantan. Data were collected through several relevant informants interviewed using the open-ended questions technique.Research findings: The results of this study indicate that APD is required to be professional to carry out their duties in managing village development, but on the other hand, the compensation for workload received is not commensurate with the risks faced. However, the increase in remuneration for the APD is only happened to the village head and village secretary, while the head of affairs and head of section’s renumeration remain below regional standard pay (UMR). The main cause of fraud is in the aspect of hegemony power and governance.Theoretical contribution/ Originality: The new remuneration system is supposed to curb the potential fraud, however, it leaves new loopholes for committing fraud. The paper suggests the new renumeration system needs to be revamped, in which all APD should receive minimum pay at UMR level, Improved governance, encouraging community participation and eliminating stereotypes about power as an effort to achieve prosperity.Research limitation/Implication: This research was conducted using a qualitative approach where the results of this study cannot be generalized to a wider scope.